PENGARUH ENDORSMENT DAN RATING REVIEW TERHADAP KEPUTUSAN PEMBELIAN DI RUMAH MAKAN IBU YATI LINGKAR BARAT KOTA BENGKULU - Agung Anugrah; Islamuddin Islamuddin (UM. Bengkulu, 2026)
The marketing strategy that is implemented needs to be evaluated and developed in accordance with market developments and the market environment. The marketing strategy must be able to provide a clear and detailed description of how the business will take advantage of every opportunity and combination of several market targets. This study aims to determine the influence of endorsements and review ratings on purchasing decisions at Ibu Yati Lingkar Barat Restaurant in Bengkulu City. This study uses a quantitative approach based on the positivist paradigm. The quantitative approach examines a specific population or sample using data collection tools, which are then analyzed statistically to test the hypotheses that have been formulated. The sample size consists of 100 respondents. The data collection techniques used are observation and questionnaires. It can be concluded that there is a positive and significant influence of Endorsements (X1) on purchasing decisions (Y) at Ibu Yati Restaurant in Lingkar Barat, Bengkulu. Two: There is a positive and significant influence of Rating Review (X2) on the purchasing decision (Y) of Ibu Yati Lingkar Barat Bengkulu Restaurant. Three: Endorsement and Rating Review together influence the purchasing decision (Y) of Ibu Yati Lingkar Barat Bengkulu Restaurant. Keywords: Endorsement, Rating Review, Purchasing Decision